Preoperative Surgical Delay and Mortality in Hip Fracture Patients: A Prospective Cohort Study of 160 Cases - Tahir Mehmood Khattak, Waseem Ahmad, Akhtar Zaman, Hamza Fareed, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Supracondylar humeral fractures (SFH) are the most common fractures of the pediatric elbow, with a peak incidence between the ages of four and nine years. The standard treatment includes closed reduction and percutaneous pinning. This study investigates the outcomes of these methods in managing SFH in children. Patients and Methods: A total of 70 children presenting with supracondylar humeral fractures (Gartland Type III) were enrolled. Patients with neurovascular injuries linked to either open or closed Gartland type-III fractures were excluded. Closed reduction was performed under general anesthesia, with elbow immobilization in extension by two plaster slabs. Data on fracture type, injury pattern, time to treatment, surgical intervention, and outcomes were recorded. Results: The mean age of patients was 4.92 ± 3.0 years. Of the 70 cases, 56 (80%) were male and 14 (20%) female. Among the 56 children with pulseless hands, 16% had Gartland Type III and 84% had Type IV fractures. The majority of hands (64%) were warm, while 36% were cold. The mean time from injury to presentation was 4.0 ± 2.5 hours. Surgical outcomes included autologous interposition venous grafting in 25%, vascular reconstruction in 60%, and segmental resection with primary anastomosis in 15%. No amputations, fasciotomies, or long-term ischemic complications occurred. Conclusion: This study confirms that closed reduction and immobilization with two slabs is a safe and effective treatment for managing Gartland Type III supracondylar fractures. Additionally, early vascular exploration can effectively treat both cold and warm pulseless hands. Keywords: Supracondylar humeral fractures, Management, Children, Close reduction approach